2020
DOI: 10.3390/en13071792
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Geothermal Resources and Geothermal Geological Characteristics in Datong Basin, Northern China

Abstract: Datong Basin is a Cenozoic fault basin located in the central part of the North China Block with strong tectonic activity. The unique geological environment of Datong Basin is believed to have good conditions for the formation of geothermal resources. Based on the research of the classification, genesis and geothermal geological characteristics of geothermal resources, the geological conditions, seismic activity, volcanic activity, geophysical exploration results, terrestrial heat flow and hot springs in Daton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The Yanggao geothermal field, located in the Datong Basin, northern Shanxi Province, has produced geothermal resources with temperatures ranging from 28 to 45 • C. These resources are Neogene and Quaternary low-temperature geothermal resources, and are primarily used for bathing. Based on the analysis of geological conditions, seismic activity, volcanic activity, terrestrial heat flow, and thermal springs, as well as geophysical exploration, it is proposed that the Datong Basin enjoys favorable geological conditions for geothermal resources and exhibits significant research value [18,20]. As regards the Yanggao geothermal field, its geological, structural, and cap rock distribution characteristics have been identified through geophysical exploration [19], and the hydrochemical characteristics and other general properties of its geothermal water have been analyzed [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The Yanggao geothermal field, located in the Datong Basin, northern Shanxi Province, has produced geothermal resources with temperatures ranging from 28 to 45 • C. These resources are Neogene and Quaternary low-temperature geothermal resources, and are primarily used for bathing. Based on the analysis of geological conditions, seismic activity, volcanic activity, terrestrial heat flow, and thermal springs, as well as geophysical exploration, it is proposed that the Datong Basin enjoys favorable geological conditions for geothermal resources and exhibits significant research value [18,20]. As regards the Yanggao geothermal field, its geological, structural, and cap rock distribution characteristics have been identified through geophysical exploration [19], and the hydrochemical characteristics and other general properties of its geothermal water have been analyzed [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Shallow geothermal energy, as a new low-carbon, clean natural energy source, is thermal energy stored in the rock-soil body, groundwater, and surface water at a specific depth range (<200 m) below the ground surface [1] that has value for exploitation. The temperature of this energy is usually below 25 • C [2], with abundant resources in China.…”
Section: Introductionmentioning
confidence: 99%
“…Many GSMs, especially warm and hot springs, geysers, and fumaroles, have drawn plenty of attention from the geothermal community in recent decades. Many researchers investigated geothermal anomalies related to GSMs such as hot springs using geophysics [9][10][11], geochemistry [12][13][14], remote sensing [15][16][17][18][19], Geographic Information System (GIS) [20], statistical modeling [21] and conventional Machine Learning (ML) [6,22,23]. For example, Gentana et al (2019) demonstrated that the fault system is correlated with the appearances of the GSMs in the Indonesia volcanic zone [24]; Freski et al (2021) tested the effects of alteration degree, moisture, and temperature on laser return intensity for the GSMs.…”
Section: Introductionmentioning
confidence: 99%